Oxidative Stress in Poultry and the Therapeutic Role of Herbal Medicine in Intestinal Health - Yuan Li; Kai Wang; Chunmei Li (MDPI AG, 2024)
The intensive broiler farming model has accelerated the development of the poultry farming industry. However, it has also inevitably brought about many stressors that lead to oxidative stress in the organism. The intestine is the leading site of nutrient digestion, absorption, and metabolism, as well as a secretory and immune organ. Oxidative stress in animal production can harm the intestine, potentially leading to significant losses for the farming industry. Under conditions of oxidative stress, many free radicals are produced in the animal's body, attacking the intestinal mucosal tissues and destroying the barrier integrity of the intestinal tract, leading to disease. Recently, herbs have been shown to have a favorable safety profile and promising application in improving intestinal oxidative stress in poultry. Therefore, future in-depth studies on the specific mechanisms of herbs and their extracts for treating intestinal oxidative stress can provide a theoretical basis for the clinical application of herbs and new therapeutic options for intestinal oxidative stress injury during poultry farming. This review focuses on the causes and hazards of oxidative stress in the intestinal tract of poultry, and on herbs and their extracts with therapeutic potential, to provide a reference for developing and applying new antioxidants.